How accounting begins: Object formation and the accretion of infrastructure - Power, Michael (Accounting, Organizations and Society, 2015)
Drawing on the case of accounting for the impact of research in UK universities, and building on key contributions to Accounting, Organizations and Society, the paper explores the conditions under which new accounting systems begin and the unfolding dynamics by which vague performance objects becoming operational. Accounting for research impact involves a radical change in the landscape of UK universities. At the centre of this change process is the progressive construction of the Impact Case Study (ICS) as a new unit of performance accountability for UK universities. Inductively, the emergence of the ICS suggests a fourfold developmental schema for accounting origination spanning field and organization level changes: policy object formation, object elaboration, activity orchestration and practice stabilization in infrastructure. Drawing upon existing scholarship, the paper uses the impact accounting setting to explore the dynamics of this developmental schema and its implications for calculation, subjectivization and the structuring of organizational temporalities. The case of impact in UK universities shows that accounting never simply begins but has multiple conditions of possibility which align as drivers for change at both field and organization levels. The case of impact accounting also reveals the significance of managerial infrastructures during accounting origination and this is suggestive of a future research agenda.